Professionalism among Intern Doctors of Different Medical College Hospitals in Bangladesh (Bangladesh Journal of Medical Education, 2017)
This descriptive cross-sectional study was conducted to explore the status of professionalism regarding knowledge, attitude and practice among intern doctors of different medical college Hospitals in Bangladesh. Study period was July 2015 June 2016.Sample size was 300 and convenient sampling technique was adopted. Study was carried out among all Bangladeshi intern doctors of 4 governments and 2 non-governments selected medical college Hospitals of Dhaka and outside Dhaka. Total 300 intern doctors responded to a self-administered questionnaire. Male female ratio was almost 1:1. Concept of professionalism and level of knowledge regarding its various aspects are not satisfactory in large extends. But attitude towards most of the major principles of professionalism are as much as positive like USA and UK physicians. However, regarding honesty with patients, one statement like physicians should disclose all significant medical errors to affected patients and/or guardians, only 36.9% agreed with this. Similarly, only 43% agreed the statement of re-certification examination to maintain professional competence. Regarding attitude and practice of major attributes & responsibilities of professionalism there is no significant difference (p>0.05) between male and female intern doctors working in different medical college hospitals; but regarding practice there is a significant difference (p